MENINGKATKAN PRODUKSI BUNGA POTONG ANTHURIUM SP MELALUI PEMANFAATAN PUPUK ORGANIK - N. L. Suriani; N. M. S. Parwanayoni; N. M. Suartini (Buletin Udayana Mengabdi, 2016)
The aim of this study was to look at the effectiveness of organic fertilizers in increasing the production of anthurium sp flowers. Method of this research a randomized block design with 4 treatments and 6 replications. Starting with the manufacture of organic fertilizers by using chicken dung and waste cut flowers. Then made an application to the anthurium flowers. Parameters measured were plant height, number of leaves, number of tillers / hill, the amount of interest / clump and flower diameter. The results that the treatment significantly different (P <0.05) with the control. This suggests that organic fertilizers can increase production of cut flower anthurium sp, with the highest amount of interest and the interest of the longest diameter contained in the fertilizer treatment of 1.5 tons / ha. Number of tillers / clump and number of leaves contained in the fertilizer treatment of 2 tons / ha, this is due to the treatment, the number of N fertilizer is too high that the increased leaf production. From the results of this study concluded that organic fertilizers can increase production of flower anthurium sp.